SISTEM INFORMASI MANAJEMEN SUMBER DAYA MANUSIA DALAM KOMUNIKASI - Atika Tantarani; Kendras Wiarsih; Rizka Nurbarokah; Serli Apriani; Reni Widyastuti (CV. ADIBA AISHA AMIRA, 2026)
This study aims to examine the role of the Human Resource Information System (HRIS) in supporting organizational communication. The research method used is a literature review by analyzing relevant scholarly articles. The findings indicate that HRIS plays an important role in facilitating fast, accurate, and integrated information delivery, as well as supporting coordination and two-way communication between management and employees. In addition to improving work efficiency and information transparency, the implementation of HRIS faces challenges related to human resource readiness, technological infrastructure, and adaptation to digital work culture.